Effects of ethylene on berry ripening and anthocyanin accumulation of 'Fujiminori' grape in protected cultivation. (13th August 2021) - Wang, Peipei; Ge, Mengqing; Yu, Aishui; Song, Wei; Fang, Jinggui; Leng, Xiangpeng
Abstract: BACKGROUND: Although the grape berries are deliberated as a non‐climacteric fruit, ethylene seems to be involved in grape berry ripening. However, the precise role of ethylene in regulating the ripening of non‐climacteric fruits is poorly understood. RESULTS: Exogenous ethephon (ETH) can stimulate the concentration of internal ethylene and accelerate the accumulation of anthocyanins in berries of 'Fujiminori', including malvidin‐, delphinidin‐, and petunidin‐derivatives (3′, 4′, 5′‐trihydroxylated anthocyanins) and cyanidin‐derivatives (3′, 4′‐dihydroxylated anthocyanins). The content of 3′, 4′, 5′‐trihydroxylated anthocyanins was extremely higher than 3′, 4′‐dihydroxylated anthocyanins, and ethylene did not affect the composition of anthocyanins in grape. Furthermore, we observed the expression of anthocyanin structural and regulatory genes as well as ethylene biosynthesis and response genes in response to ETH treatment. The anthocyanins accumulation is significantly associated with increased expression of anthocyanin structural ( VvPAL, Vv4CH, VvCHS, VvCHI, VvF3H, and VvUFGT ) and regulatory genes ( VvMYBA1, VvMYBA2, and VvMYBA3 ), which persisted over the 12 days. In addition, exogenous ETH affected the endogenous ethylene biosynthesis ( VvACO2 and VvACO4 ) and the downstream ethylene regulatory network ( VvERS1, VvETR2, VvCTR1, and VvERF005 ). CONCLUSIONS: These findings bring new insights into the physiological and molecular function of ethylene during berry development and ripening in grapes. © 2021 Society of Chemical Industry